Processed data from Limited vocal compensation for elevated ambient noise in bearded seals: implications for an industrializing Arctic ocean - Michelle E. H. Fournet; Margherita Silvestri; Christopher W. Clark; Holger Klinck; Aaron N. Rice (2021)
Data used for statistical analysis, data summary, and modeling